The Effectiveness of Technology Integration in Arabic Language Learning: Systematic Literature Review - Fadli Lubis, Adi; Nasution, Sahkholid (Ihya al-Arabiyah: Jurnal Pendidikan Bahasa dan Sastra Arab, 2024)
The advancement of technology has brought significant transformation to the field of education, including Arabic language learning. This study examines the effectiveness of technology integration in Arabic language learning through a Systematic Literature Review (SLR) approach, following the guidelines of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). The study aims to analyze the impact of technological implementations such as Artificial Intelligence (AI), Augmented Reality (AR), gamification, and online learning platforms on enhancing student engagement, comprehension, and motivation. The findings indicate that technology utilization not only enriches the learning experience and provides flexibility in accessing materials but also significantly improves overall learning effectiveness. However, its implementation still faces several challenges, including limited infrastructure, inadequate teacher readiness, and cultural and curriculum gaps within the education system. Therefore, this study recommends continuous teacher training, investment in digital infrastructure, and curriculum updates to ensure better adaptation to technological advancements. In the future, innovations such as Virtual Reality (VR) and personalized AI hold great potential for creating more interactive, immersive, and effective Arabic language learning experiences.